2000
DOI: 10.1074/jbc.m910091199
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Gyrase, the Two Domains Intimately Cooperate to Promote Positive Supercoiling

Abstract: Reverse gyrases are atypical topoisomerases present in hyperthermophiles and are able to positively supercoil a circular DNA. Despite a number of studies, the mechanism by which they perform this peculiar activity is still unclear. Sequence data suggested that reverse gyrases are composed of two putative domains, a helicase-like and a topoisomerase I, usually in a single polypeptide. Based on these predictions, we have separately expressed the putative domains and the fulllength polypeptide of Sulfolobus acido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 27 publications
3
92
1
Order By: Relevance
“…The topoisomerase domain expressed on its own does weakly relax DNA in the absence of ATP (Fig. 5D), as reported for the topoisomerase domain of S. acidocaldarius reverse gyrase (21). These results indicate that the N-terminal domain represses the activity of the topoisomerase domain in the absence of nucleotide.…”
Section: Dna Binding Behavior-supporting
confidence: 67%
See 2 more Smart Citations
“…The topoisomerase domain expressed on its own does weakly relax DNA in the absence of ATP (Fig. 5D), as reported for the topoisomerase domain of S. acidocaldarius reverse gyrase (21). These results indicate that the N-terminal domain represses the activity of the topoisomerase domain in the absence of nucleotide.…”
Section: Dna Binding Behavior-supporting
confidence: 67%
“…A contrasting explanation for the unidirectionality is provided by the "domain model" (6). Reverse gyrase is known to unwind DNA locally upon binding (9,21), and the domain model stipulates that the enzyme can isolate this unwound DNA topologically from the rest of the substrate. In DNA that is topologically constrained as a whole, such as a plasmid, the creation of unwound DNA at the protein binding site creates compensatory overwinding elsewhere.…”
Section: Fig 8 Topoisomerization Activity Of Reverse Gyrase Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse gyrase, an enzyme first discovered in the hyperthermophilic archaeon Sulfolobus acidocaldarius, is formed by the combination of an N-terminal helicase module and a C-terminal topoisomerase module (see Declais et al 2000 for a review). Comparative genomic analysis performed 4 years ago showed that reverse gyrase was at that time the only protein specific for hyperthermophiles (i.e., present in all hyperthermophiles and absent in all non-hyperthermophiles) (Forterre 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Reverse gyrase is found in hyperthermophilic archaea and eubacteria, and the positive supercoiling activity requires a temperature above 70°C (8,9). The enzyme is a 130-kDa single polypeptide, a fusion complex of two domains (10): The carboxyl terminal half is related to topo IA, whereas the amino terminal half has an ATP-binding site and is akin to helicase, although neither the whole enzyme nor the isolated helicase-like domain shows genuine helicase activity (11). A crystal structure of the full-length reverse gyrase (12) and more recent structures with additional features (13) all support the basic two-domain construct.…”
mentioning
confidence: 99%